زرعی پیداوار کی مارکیٹنگ کی مروجہ صورتیں اور شریعت اسلامیہ کی روشنی میں ان کا تجزیہContemporary Types of Agricultural Marketing from the Perspective of Islamic Jurisprudence (Al-Qamar, 2021)
Islamic approach to marketing is different from the western approach. The western approach sees it ‘as it is’ eg, how commodities are being marketed? On the other hand, Islamic principles of marketing approach things from a different perspective of how things should be marketed, according to Islamic way of marketing. The following discussion takes in to account the present marketing situation in Pakistan. Regretfully, in Pakistan which came into being in the name of Islam, the Islamic principles of marketing kept getting neglected resulting in a very precarious situation in which every stake holder participates in marketing practice from the perspective of their respective ‘profit’ even at the cost of other stake holders resulting in a very exploitative situation. The Islamic principles of marketing take in to account the criterion of halal (permitted) versus haram (prohibited) in marketing dealings. This distinction between halal and haram is based on the element of ‘interest’ which makes business dealing lawful or unlawful. The defining feature of Islamic concept of marketing is ‘Ihsan’ rather than ‘interest’ which is the associated with the western concept of interest.
Keywords: Western; commodities; precarious; criterion of Halāl; ‘Ihsan'; interest